2020
DOI: 10.1159/000512636
|View full text |Cite
|
Sign up to set email alerts
|

Sickle Cell Maculopathy: Prevalence, Associations and Impact on Visual Acuity

Abstract: Aims: To investigate the prevalence of sickle cell maculopathy (SCM), associations with age, sex, genotype and proliferative sickle cell retinopathy (PSR) stage and the impact on visual acuity Methods: Age, sex and visual acuity were recorded and spectral domain OCT and ultra-widefield images of the macula and retina were reviewed for a consecutive series of 74 adults with sickle cell disease Results: The median age was 37 years (range 19-73 years) and 36 cases (48.6%) were male. SCM was present in at least … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…2 shows the hazard ratios of HbSC to HbSS and HbSβ 0 thal for each of the individual disease-related chronic conditions. In keeping with previous reports 24 , 25 , compared to those with HbSS and HbSβ 0 thal, patients with HbSC were more likely to develop retinopathy ( P < 0.0001). However, their risks for chronic kidney disease ( P = 0.014), pulmonary hypertension ( P = 0.0075) and chronic leg ulcers ( P = 0.001) were lower.…”
Section: Resultssupporting
confidence: 91%
“…2 shows the hazard ratios of HbSC to HbSS and HbSβ 0 thal for each of the individual disease-related chronic conditions. In keeping with previous reports 24 , 25 , compared to those with HbSS and HbSβ 0 thal, patients with HbSC were more likely to develop retinopathy ( P < 0.0001). However, their risks for chronic kidney disease ( P = 0.014), pulmonary hypertension ( P = 0.0075) and chronic leg ulcers ( P = 0.001) were lower.…”
Section: Resultssupporting
confidence: 91%
“…This frequency is in accordance with previous values that exhibit large variation from 53.6% to 29%. 7,11,17 None of our patients had a symptomatic visual impairment. 4 However, different authors reported asymptomatic involvement of the visual field and contrast sensibility.…”
Section: Discussionmentioning
confidence: 81%
“…But, when tested, patients with SCD with such abnormalities exhibit decrease in retinal sensitivity, visual field defects, and perturbation of contrast sensitivity. 10,11 Several questions regarding this macular or parafoveal involvement are still unsolved. It has been suggested that they could share the same mechanism as silent border zone cerebral infarct.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Factors examined for an association with the development of SCR and PSCR included: gender, hemoglobin genotype, blood pressure (BP), body mass index (BMI), the presence of systemic SCD complications (e.g., seizure, cerebrovascular accident [CVA], hematuria, nephrotic syndrome, hearing loss, heart disease, hand foot syndrome, spleen infarction, pneumonia, lung infarction, leg ulcers, or previous painful crisis), smoking history (including the use of cigarettes, cigars, and/or pipes) and hematological laboratory testing (e.g., WBC, platelets, and reticulocyte counts, hemoglobin, and HbF levels) [10,[17][18][19][20][21][22]. BP was considered to be abnormal if systolic pressure was ≥ 130 mmHg or diastolic pressure was ≥ 90 mmHg.…”
Section: Methodsmentioning
confidence: 99%